THE INFLUENCE OF HEALTH INFORMATION ON KNOWLEDGE ABAOUT PREEKLAMPSIA - Septiani, Tety; Makiyah, Sri Nabawiyati Nurul; Attamimi, Ahsanudin (LPPM Universitas Prima Nusantara Bukittinggi, 2020)
Background: Pre-eclampsia is a very serious medical condition that can affect around 3-5% of pregnancies. More than 35,000 maternal deaths each year worldwide are caused by preeclampsia.Method: The authors identify studies that explain the effect of health information about knowledge about preeclampsia from several databases namely PubMed, ProQuest, EBSCO. Searches are limited to studies published in English and present data for the 2010-2020 period. The identified study was reviewed using PRISMA Flowchart. Studies with related quantitative designs about the effect of health information and risk factors for preeclampsia preeclampsia are selected for review.Results: as many as eight articles reviewed were found with two sub-themes, namely the factors causing preeclampsia, namely age, parity, obesity and a history of hypertension and health information about preeclampsia.Conclusion: All impacts related to the occurrence of the risk of preeclampsia can cause an increase in maternal and infant morbidity. Therefore, due to the many factors that can cause preeclampsia, it is recommended that all women, especially in developing countries, routinely check for pregnancy or integrated ANC in existing health facilities and health workers always provide information related to the risks and impacts that occur if the mother experiences preeclampsia.